Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.ejmech.2014.09.082
|View full text |Cite
|
Sign up to set email alerts
|

Selection of an optimal cysteine-containing peptide-based chelator for labeling of affibody molecules with 188Re

Abstract: Affibody molecules constitute a class of small (7 kDa) scaffold proteins that can be engineered to have excellent tumor targeting properties. High reabsorption in kidneys complicates development of affibody molecules for radionuclide therapy. In this study, we evaluated the influence of the composition of cysteine-containing C-terminal peptide-based chelators on the biodistribution and renal retention of (188)Re-labeled anti-HER2 affibody molecules. Biodistribution of affibody molecules containing GGXC or GXGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…This indicated that the main reason of the release was re-oxidation of technetium. This was not what we have observed earlier for anti-HER2 and anti-IGF-1R affibody molecules, where even -GGGC provided a stable attachment of 99m Tc and 188 Re (Wållberg et al 2011; Altai et al 2012, 2014a, b; Mitran et al 2015). A possible explanation for the current results is that some side chains in the affibody molecules form an alternative chelating pocket and a part of technetium is bound not only to a cysteine-containing chelator, but also to this much weaker site.…”
Section: Discussioncontrasting
confidence: 67%
“…This indicated that the main reason of the release was re-oxidation of technetium. This was not what we have observed earlier for anti-HER2 and anti-IGF-1R affibody molecules, where even -GGGC provided a stable attachment of 99m Tc and 188 Re (Wållberg et al 2011; Altai et al 2012, 2014a, b; Mitran et al 2015). A possible explanation for the current results is that some side chains in the affibody molecules form an alternative chelating pocket and a part of technetium is bound not only to a cysteine-containing chelator, but also to this much weaker site.…”
Section: Discussioncontrasting
confidence: 67%
“…The present study evaluated preconditions to labeling of affibody molecule-derived imaging probes using peptide-based cysteine-containing chelators. Chelators of that type provided a stable labeling of anti-HER2 affibody molecules with 99m Tc and 188 Re (42,52). An apparent advantage of such chelators is that they are ‘built in’ in the recombinantly produced affibody molecule, and there is no need in additional steps of coupling of the chelator and purification of the conjugate.…”
Section: Discussionmentioning
confidence: 99%
“…An apparent advantage of such chelators is that they are ‘built in’ in the recombinantly produced affibody molecule, and there is no need in additional steps of coupling of the chelator and purification of the conjugate. In addition, selection of amino acids in the chelator may enable a fine-tuning of residualizing properties of the label (5254). However, there was a risk of losing site-specificity of the label when amino acid composition of an affibody molecules was modified (43).…”
Section: Discussionmentioning
confidence: 99%
“…In order to deliver the required dose to tumors without exceeding the limiting dose to the kidneys (23 Gy), several strategies have been developed. The use of labeling approaches that provide nonresidualizing radiocatabolites, such as radioiodination [5,6] or the use of some peptide-based chelators for rhenium radioisotopes and technetium-99m [12][13][14][15][16][17], was shown to decrease the retention of activity in the kidneys by several folds and to improve tumor-to-kidney ratios. Another effective strategy is the fusion of an ESP to an albumin-binding domain (ABD).…”
Section: Introductionmentioning
confidence: 99%